Antibacterial properties of selected mangrove plants against vibrio species and its cytotoxicity against artemia salina - Ahmad, Ahmad Shamsuddin; Musa, Najiah; Assaw, Suvik; Mohtar, Noor Azariyah; Yunus, Kamaruzzaman; Abd. Wahid, Mohd. Effendy; John, Akbar (IDOSI Publication, 2013)
Emerging antibiotic resistance among the pathogenic microorganism has triggered the discovery of various antimicrobial compounds from marine source. Secondary metabolites from plants especially mangroves is traditionally being used widely as antimicrobials. Hence, present study was aimed to determine the antibacterial and cytotoxic properties of the selected mangrove plant leaves (Bruguiera cyclindrica, Sonneratia caseolaris, Luminitzera racemosa, Rhizophora apiculata, Avicennia alba, Acrostichum aureum, Nypa fruticans, Pandanus odoratissimus, Hibiscus tiliaceous and Derris trifoliate) against aquaculture pathogenic strains of genus. Methanol and aqueous extracts of leaves samples were prepared. The antibacterial activity was determined by using disc diffusion method against six pathogenic Gram-negative Vibrio species, such as Vibrio alginolyticus and V. parahaemolyticus (isolated from Scylla serrata, mangrove crab), V. alginolyticus and V. parahaemolyticus (from Giant prawn), V. alginolyticus (from Tiger prawn) and also V. parahaemolyticus (from Reference strain ATCC 17802). Methanolic extracts of S. caseolaris produced significant inhibition zone against all the pathogenic Vibrio spp. except for V. parahaemolyticus (from Giant prawn). Minimum inhibitory concentration test (MIC) and cytotoxicity (LC50) test using Artemia salina as a test animal in sterile ELISA (Enzyme-Linked Immunosorbent Assay) microplates showed the significant antimicrobial properties of methanolic extract of S. caesolaris. Overall, present study proved the active antimicrobial compounds in methanolic extract of S. caesolaris which could be used against Vibrio pathogens in aquaculture.